2021
DOI: 10.1075/ijcl.21096.mul
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the unknown

Abstract: This paper presents an annotation approach to examine uncertainty in British and German newspaper articles on the coronavirus pandemic. We develop a tagset in an interdisciplinary team from corpus linguistics and sociology. After working out a gold standard on a pilot corpus, we apply the annotation to the entire corpus drawing on an “annotation-by-query” approach in CQPWeb, based on uncertainty constructions that have been extracted from the gold standard data. The annotated data are then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Hedges, as shown in Table 3, were significantly more frequent in the Covid‐19 highlights ( U = 51,090, z‐statistic = 3.3629, p < 0.001) which, to some extent, indicates academics’ awareness of the high degree of uncertainty surrounding research into the pandemic. Uncertainty is key to the social management of public health risk (Müller et al., 2021) and hedges point to the degree of caution that should be associated with claims. In the Covid highlights, hedges were more frequently used to express scientific possibility or predication and show considerable uncertainty about the potential measures that can be taken with the coronavirus pandemic.…”
Section: Stance: Results and Discussionmentioning
confidence: 99%
“…Hedges, as shown in Table 3, were significantly more frequent in the Covid‐19 highlights ( U = 51,090, z‐statistic = 3.3629, p < 0.001) which, to some extent, indicates academics’ awareness of the high degree of uncertainty surrounding research into the pandemic. Uncertainty is key to the social management of public health risk (Müller et al., 2021) and hedges point to the degree of caution that should be associated with claims. In the Covid highlights, hedges were more frequently used to express scientific possibility or predication and show considerable uncertainty about the potential measures that can be taken with the coronavirus pandemic.…”
Section: Stance: Results and Discussionmentioning
confidence: 99%
“…Studies that have examined the language of Covid-19 include works aiming to describe, for example, the use of uncertainty constructions in media discourse (Müller et al, 2021) or networked discourses of bereavement in online Covid-19 memorials (McGlashan, 2021). They have demonstrated that language "can provide evidence of social experiences of the pandemic" (Mahlberg and Brookes, 2021, p. 441).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The language used during the COVID-19 era can provide insight into these profound and far-reaching changes that resulted from the pandemic directly or indirectly. Linguistic research has explored public health messaging from the government and related agencies (e.g., Kalocsányiová et al, 2021 ; Strange, 2022 ) and the media (Jaworska, 2021 ; Müller et al, 2021 ; Semino, 2021 ; Yu et al, 2021 ; Kania, 2022 ; Bafort et al, 2023 ; Giorgis et al, 2023 ). A number of studies analyse COVID-19 signage communication, such as Tragel and Pikksaar ( 2022 ) and Bagna and Bellinzona ( 2023 ).…”
Section: Introductionmentioning
confidence: 99%